(Re)-Building Educational Trust: Young NEET and the Importance of Trust Relations. Issue 3 (2nd October 2021) - Görlich, Anne
Abstract: In Denmark as in Europe at large, there is a continued need for interventions helping young NEET (Not in Education, Employment or Training) into ordinary education. At the core of the educational challenges of young NEET is the breakdown of trust, which highlights the need for re-building trust as crucial for the success of the interventions. Building on 14 focus group interviews with 98 young NEET, the analysis will explore trust and vulnerability in learning situations.